The Use of Picture-Kwl Technique in Improving Students’ Reading Comprehension: A Cooperative Learning Approach - Mutakhirani Mustafa (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The objective of this research was to find out whether the use of Picture-KWL technique in improving students’ reading comprehension: a cooperative learning approach could improve the reading comprehension and the interest of the students in reading. The design of this research is quasi experimental which the experimental group would be employed treatment Picture-KWL in cooperative learning approach while the control group would be employed treatment using conventional techniques by the researcher. The findings indicated that the experimental class scored higher on the reading comprehension in post-test than their peers did in the control class. The researcher concluded that the technique was successful in improving the reading comprehension performance and recommended that the technique should be integrated into the English Syllabus specially in teaching reading comprehension. Moreover, based on the students’ respond on questionnaire, it shows that the students’ interest was categorized as interested. And also observation showed that the students’ progress were excellent in the classroom during learning progress.